2017
DOI: 10.1186/s40169-017-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions for rapid clinical‐scale expansion of human umbilical cord blood‐derived mesenchymal stem cells

Abstract: Background Mesenchymal stem cells (MSCs) have broad-spectrum therapeutic effects in various diseases, and thus have many clinical applications. However, it is difficult to produce sufficient numbers of MSCs for clinical use, and improved culture systems are required. Here, we report the effects of calcium (Ca 2+ ) and hypoxia on the proliferation of human umbilical cord blood-derived MSCs (hUCB-MSCs). In addition, we determined the optimal conditions of these two factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Treatment of extracellular calcium has also been shown to increase the extent of calcium influx through the calcium channel [ 37 ]. Therefore, to examine the causative role of Ca 2+ in hUCB-MSCs adipogenic differentiation, the cells were treated with calcium chloride (1.8 mM) to elevate the intracellular Ca 2+ level during 5 days of culture (i.e., one passage culture of MSCs-H or MSCs-L, Supplementary Figure 5 ) [ 38 ]. Furthermore, the cells were pretreated with 5 μ M BAPTA-AM, which is a cell-permeant intracellular Ca 2+ chelator, for 2 h. To analyze whether Ca 2+ or BAPTA-AM treatment altered the MSC characteristics of the cells, the expressions of MSC-specific antigens and multilineage differentiation factors were compared in the different treatment groups (see Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of extracellular calcium has also been shown to increase the extent of calcium influx through the calcium channel [ 37 ]. Therefore, to examine the causative role of Ca 2+ in hUCB-MSCs adipogenic differentiation, the cells were treated with calcium chloride (1.8 mM) to elevate the intracellular Ca 2+ level during 5 days of culture (i.e., one passage culture of MSCs-H or MSCs-L, Supplementary Figure 5 ) [ 38 ]. Furthermore, the cells were pretreated with 5 μ M BAPTA-AM, which is a cell-permeant intracellular Ca 2+ chelator, for 2 h. To analyze whether Ca 2+ or BAPTA-AM treatment altered the MSC characteristics of the cells, the expressions of MSC-specific antigens and multilineage differentiation factors were compared in the different treatment groups (see Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is imperative to develop methods that can maintain MSCs without losing their self-renewal and differentiation potential. A number of studies have reported large-scale production of MSCs for clinical and commercial usage by devising newer methods such as three-dimensional (3-D) culture, bioreactors, hypoxic conditions, and the addition of growth factors (Choi et al, 2017;Dayment et al, 2014;Gottipamula, Muttigi, Kolkundkar, & Seetharam, 2013;Sart & Agathos, 2016;Swamynathan et al, 2014). Using a microcarrier-based suspension system, MSCs were amplified to a 10 3 -fold increase, which was significantly higher as compared with the 200-fold increase in monolayer culture (Yuan, Kallos, Hunter, & Sen, 2014).…”
Section: Challengesmentioning
confidence: 99%
“…Maintenance and self-renewal (K. A. Jackson et al, 2001;Law & Chaudhuri, 2013) Large-scale production for clinical and commercial usage (Choi et al, 2017;Gottipamula et al, 2013;Sart & Agathos, 2016;Swamynathan et al, 2014) Standardization of criteria for characterization (Robey, 2017;Sacchetti et al, 2016) Differentiation of MSCs in vitro and in vivo (Alimperti, You, George, Agarwal, & Andreadis, 2014;K. A. Jackson et al, 2001) Homing and localization to the sight of injury (Fiumana et al, 2013;Young, Flynn, & Amsden, 2018) Cell survival and integration in vivo (J.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Preparation of hUCB-MSCs. This study was approved by the Institutional Review Board of MEdIPOST co., Ltd. collection of hUcB and isolation and culture of hUcB-MScs were performed as previously described (22). Mononuclear cells were isolated from hUcBs by centrifugation on a Ficoll-Hypaque gradient (density, 1.077 g/cm 3 ; Sigma-Aldrich; Merck KGaA).…”
Section: Methodsmentioning
confidence: 99%